2000
DOI: 10.1364/ol.25.000414
|View full text |Cite
|
Sign up to set email alerts
|

Electrically controlled surface diffraction gratings in nematic liquid crystals

Abstract: Photorefractive diffraction gratings were studied in cells of homeotropically aligned pentyl-cyanobiphenyl liquid crystal. These holographic gratings were induced by the simultaneous and nonsimultaneous application of dc and coherent optical electric fields. The observed behavior was consistent with a predominantly surface-mediated photorefractive effect. Beam coupling was observed in all cases and led to a model involving screened and unscreened interfacial trapped charges driving a modulation of the easy axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 4 publications
3
55
0
Order By: Relevance
“…Photorefraction in liquid crystals has recently attracted significant attention since it is characterized with strong optical nonlinearities at low light intensities and voltage [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Currently, liquid crystalline materials are considered a leading candidate for those applications that do not require long storage times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photorefraction in liquid crystals has recently attracted significant attention since it is characterized with strong optical nonlinearities at low light intensities and voltage [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Currently, liquid crystalline materials are considered a leading candidate for those applications that do not require long storage times.…”
Section: Introductionmentioning
confidence: 99%
“…Tabiryan et al proposed to use a photorefractive aligning surface with this aim [10]. Singer, Reshetnyak, Reznikov et al found that surface-mediated effect could also arise if photo-induced charges in the aligning layers changed the distribution of ions in the LC bulk [11] or due to the photochemical reaction on the aligning surface [12]. It was shown recently that surface mediated photorefractivity can be also initiated due to a light-induced adsorption of fullerene-based dopant [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several types of LC optical elements have been proposed [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The needed spatial distribution of the LC director is achieved in the majority cases by means of an inhomogeneous electric field [1][2][3][4][5][6][7][8][9][10][11][12] or with a thickness variations [1,2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The needed spatial distribution of the LC director is achieved in the majority cases by means of an inhomogeneous electric field [1][2][3][4][5][6][7][8][9][10][11][12] or with a thickness variations [1,2,13,14]. Adaptation of such approaches for micron-scaled systems poses technological difficulties due to that electrodes are required or due to geometrical non-uniformities.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by doping a polymer layer with dye, such as azo-dye, gratings can be also written directly into that layer [20]. It was also shown that the diffraction efficiency of such doped-polymer-mediated gratings can be varied (but not enhanced) by application of an ac/dc field [12], [24]. Patterns [3], [23] written in cells without special coating of the cell surfaces persisted in time, but typically decayed over a period of a few hours.…”
Section: Introductionmentioning
confidence: 99%